The Implications of Political Factor on Construction Risk Management: The Perspectives of Construction Companies in Nigerian - Adeleke, A. Q.; A. Y., Bahaudin; A. M., Kamarudeen; Bamgbaded, J. A.; Salimon, Maruf Gbadebo (Universiti Utara Malaysia, 2017)
Various inconsistent assertions has been opined by momentous previous studies concerning the influence of political factor on risk management in construction projects, with moderating effects of rules and regulations towards the inconsistency preceding results. Hence, this study examined the aforesaid statements grounded on organizational control theory. Structured survey questionnaires of 238 employees working in Nigeria construction companies was used to gather this data. PLS-SEM was used to analyse the data and a significant positive results was revealed between political factor and construction risk management. Similarly, a significant positive relationship of rules and regulations as a moderator was revealed on political factor and construction risk management.